Third Teacher goes Raumwerkstatt - participatory planning processes to redesign physical learning spaces - Lars Schlenker; Carmen Neuburg (Interaction Design and Architecture(s), 2019)
The transdisciplinary research project Lehrraum_digital[Lecture Room_digital] at the TU Dresden concentrated on developing and testing participatory methods and instruments to plan and design physical teaching and learning environments for vocational education and training (VET) considering the progressive digitalization of education. This paper presents case studies that were carried out at VET institutions in 2017 as the main part of the project. A special workshop format called Raumwerkstattis the primary focus of the paper. The workshop was developed within the project Lehrraum_digitaland, with regard to the relevance of physical learning environments in VET, it was conducted in the form of case studies with trainees and apprentices.